2004
DOI: 10.3354/meps268069
|View full text |Cite
|
Sign up to set email alerts
|

Population ecology of the invasive kelp Undaria pinnatifida in California: environmental and biological controls on demography

Abstract: We combined field monitoring and laboratory experiments to examine the population ecology of both the microscopic and macroscopic stages of a new invasion of Undaria pinnatifida in California. Over the course of 1 yr, we observed 2 distinct recruitment pulses of individuals in the Santa Barbara harbor; the appearance of these pulses was strongly correlated with a 4°C drop in ocean temperature approximately 2 mo prior to recruitment. Cultures of zoospores and successive microscopic stages revealed thermal toler… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
55
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(60 citation statements)
references
References 45 publications
(50 reference statements)
4
55
0
1
Order By: Relevance
“…To date, the majority of studies on invasive species have been conducted within their introduced ranges, and ecologists often know little about the ecology of such species in their native ranges (Hierro et al 2005). A few studies have shown that invasive species behave differently in their new range (Perez et al 1988, Hay & Villouta 1993, Thornber et al 2004, but whether that is due to a plastic response to a new environment, genetically controlled shifts in traits, founder effects, or various other factors remains uncertain.…”
Section: Introductionmentioning
confidence: 99%
“…To date, the majority of studies on invasive species have been conducted within their introduced ranges, and ecologists often know little about the ecology of such species in their native ranges (Hierro et al 2005). A few studies have shown that invasive species behave differently in their new range (Perez et al 1988, Hay & Villouta 1993, Thornber et al 2004, but whether that is due to a plastic response to a new environment, genetically controlled shifts in traits, founder effects, or various other factors remains uncertain.…”
Section: Introductionmentioning
confidence: 99%
“…tomentosoides and Caulerpa taxifolia (reviewed in Walker & Kendrick, 1998;Siguan, 2003;see also, Jousson et al, 1998;Trowbridge & Todd, 1999a, b;Meusnier et al, 2002;Thornber et al, 2004;Provan et al, 2005;Voisin et al, 2005). Two examples of older introductions (>100 years ago) are Fucus evanescens and F. serratus, both of which are major components of rocky intertidal communities on North Atlantic shores.…”
Section: Introductionmentioning
confidence: 99%
“…pinnatifida (Laminariales, Alariaceae), otherwise known as the edible seaweed wakame, is an Asian species native to Japanese, Korean, and Chinese waters, where it is extensively cultivated. The first observation of this species outside its native Asian range was recent (1971, (31); slow longdistance spread in European marinas, concomitant with the presence of wakame farms in Brittany, France (32); and heavy proliferation and naturalization in both harbors and natural subtidal zones in Australasia (28,33,34) and Argentina (35). The rapid spread of the species within regions of introduction is thought to be linked to its biological characteristics (i.e., annual life history, high growth rates, and high fecundity), typical of pioneer species (36).…”
mentioning
confidence: 99%
“…Despite increased public awareness and, in some cases, legislative measures, until now the few empirical studies of U. pinnatifida have concentrated on spread and local ecological dynamics (26,31,33). However, phylogeographic analyses lend insight into the mechanisms of introduction, colonization, and spread of invaders (23).…”
mentioning
confidence: 99%